PENGARUH FRAKSI VOLUME DAN ORIENTASI PADA KOMPOSIT SERAT GAMBAS SERTA TEBU TERHADAP KEKUATAN BENDING - Zamheri, Ahmad; Seprianto, Dicky; Sailon, Sailon; Tamilio, Hopay; Andika, Ekki; Ramadoni, Rizki (AUSTENIT, 2023)
The purpose of this study is to determine the influence of volume fractions and orientation directions on the composite of gambas fiber and sugarcane fiber on bending strength. In this study, the variation in the volume fraction of resin, gambas fiber, and sugarcane fiber was (Resin 60%: Sugarcane Fiber 20%: Gambas Fiber 20%), (Resin 70%: Sugarcane Fiber 15%: Gambas Fiber 15%), and (Resin 80%: Sugarcane Fiber 10%: Gambas Fiber 10%) with the orientation direction of gambas fiber and sugarcane fiber 90°/90°, 90°/45°and 90°/0°. In this test, the bending test specimen was made according to the ASTM D 790-02  standard and the test result data were analyzed using the Two-Way ANOVA method assisted by Microsoft Exel software. This study showed that the volume fraction (Resin 60%: Sugarcane Fiber 20%: Gambas Fiber 20%) and the orientation direction of gambas fiber and sugarcane fiber 90°/90° have  the best bending strength  which is 48.33 (N/,) this value is higher than that of Multiplex with a bending strength value of  26,60 MPa.